Pengembangan Modul Berbasis Blended Learning Pendidikan Agama Buddha Materi Kelas VII Semester Ganjil di SMP Kabupaten Blitar - Dwi Aningsih; Hesti Sadtyadi; Widia Darma (Cetta: Jurnal Ilmu Pendidikan, 2023)
Students who have grown accustomed to online instruction may experience cognitive dissonance while transitioning back to traditional classroom settings due to Covid-19's oversight. The creation of a blended learning module that incorporates online and in-person instruction is one approach to resolving the issue of how to carry out the learning process. This research set out to answer two questions: (1) how one might go about creating a blended learning module, and (2) whether or not such a module might be used effectively to teach Buddhist religious education content to seventh-semester middle school. Cennamo and Kalk's Spiral model is used for this study. In the spiral model, you first define the problem, then create a solution, then show how it works, and last deliver the solution. The average proportion, based on questionnaire data from large-scale experiments, was 92.24%. This blended learning module of Buddhist religious education has been found to be quite viable in order to be used for seventh grade students in junior high schools in Blitar Regency, as per the previously established requirements. Blended learning-based module solutions are suitable for usage as demonstrated by the results of completed questionnaires from content experts and media experts. The average percentage acquired in the massive study, as calculated by the table data from the questionnaires, was 92.24%. The integrated learning module for Buddhist religious education has been found to be quite viable in order to be used and applied to pupils in Blitar Regency's seventh grade of junior high school. After that, SPSS factor analysis indicated that the KMO and Bartlett's Test values were both more than 0.5, indicating that the product was viable. As a result, the study determines that the module can be used.